Penggunaan Heparin Dosis Tinggi pada Pasien COVID-19 dengan ARDS di Unit Perawatan Intensif (ICU) RS Darurat Wisma Atlit - Hardiyanti, Vien (SCRIPTA SCORE Scientific Medical Journal, 2022)
Background: An outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that began in Wuhan, China has spread rapidly in multiple countries of the world and has become a pandemic. The severe acute respiratory syndrome-corona virus-2 (SARS-CoV-2) infection has been associated with significantly deranged coagulation parameters and increased incidence of thrombotic events. Case: Herein, we reported a 46-year-old morbidly obese man with acute respiratory distress syndrome (ARDS) of COVID who survived the disease. Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) assay of nasopharyngeal and oropharyngeal swabs were positive for SARS-CoV-2. Diagnosis of ARDS was also according to clinical symptoms, laboratory and chest radiograph. The patient was referred to Intensive Care Unit (ICU) and received heparin therapy with therapeutic doses are based on the aPTT levels. After 20 days of intensive care, the patient showed a significant improvement. Discussion: A coagulopathy has been reported in up to 50% of patients with severe COVID-19 manifestations. COVID-19-induced hypercoagulability has been demonstrated to play a significant role in overall COVID-19 outcomes. Current literature shows promising evidence with the use of therapeutic anticoagulation in high-risk individuals. Conclusion: In patients who present with severe COVID-19 with respiratory failure, pharmacological prophylactic anticoagulants can help prevent venous thromboembolism and other thrombotic events. Keywords: ARDS, coagulopathy, COVID-19, heparin, thrombosis Latar belakang: Penyebaran virus corona 2019 (COVID-19) yang disebabkan oleh severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) yang bermula di Wuhan, Cina menyebar dengan cepat ke berbagai negara di dunia dan menjadi sebuah pandemik. Infeksi virus corona diteliti berkaitan dengan adanya gangguan koagulasi dan peningkatan risiko trombosis. Kasus: Dalam laporan kasus ini, akan dipaparkan tentang kasus corona yang terjadi pada pria berusia 46 tahun terkonfirmasi COVID dengan Acute Respiratory Distress Syndrome (ARDS) berat yang sembuh dari penyakit tersebut. Uji real-time reverse transcriptase-polymerase chain reaction (RT-PCR) sampel nasofaring dan orofaring menunjukkan hasil positif SARS-CoV-2. Diagnosis ARDS juga sesuai dengan gejala klinis, laboatorium, dan fototoraks. Pasien kemudian dirawat di ruang rawat intensif (ICU) dan mendapat terapi heparin yang disesuaikan dengan level aPTT. Setelah 20 hari perawatan intensif, pasien menunjukkan perbaikan yang signifikan. Diskusi: Kasus koagulopati dilaporkan lebih dari 50% pasien dengan COVID-19 yang berat. Hiperkoagulopati yang dipengaruhi oleh COVID-19 memainkan pengaruh yang signifikan pada hasil akhir dari penyakit tersebut. Studi pustaka terbaru menunjukkan bukti yang menjanjikan tentang penggunaan antikoagulan pada individu yang berisiko tinggi. Kesimpulan: Pada pasien COVID-19 gejala berat dengan ancaman gagal napas, antikoagulan profilaksis dibutuhkan untuk mencegah kejadian venous tromboembolism dan kasus trombosis lainnya. Kata Kunci: ARDS, COVID-19, heparin, koagulopati, trombosis